The Digital Transformation in The Music Industry: A Qualitative and Quantitative Study in The Republic of Moldova - Iurie BADICU; Tatiana COMENDANT (Communications of International Proceedings, 2024)
The digital transformation has caused significant changes in the music industry globally, also influencing the music sector in the Republic of Moldova. The research in question examines how digitization has changed the dynamics of music production, distribution and consumption in the country. The main objective of the paper is to analyze the impact of digital technologies on the music industry in the Republic of Moldova, to identify the opportunities and challenges brought by this transformation. The study is based on a combination of qualitative and quantitative methods, including sociological research into functional sectors of the domestic music industry, analysis of streaming data, as well as literature review on global and local trends in the music industry. The results indicate the dependence on streaming platforms and the need to develop digital skills among professionals in the field. It also highlights the role of social media in promoting artists and distributing music. Digital transformation offers new opportunities for Moldovan artists to access international markets and monetize their creativity through various digital channels. However, the challenges of digital transformation remain important obstacles that need to be addressed to ensure the sustainable development of the music industry.
Keywords: digital transformation; music industry; Republic of Moldova; streaming